2020
DOI: 10.3390/w12061755
|View full text |Cite
|
Sign up to set email alerts
|

Phycoremediation of Landfill Leachate with Desmodesmus subspicatus: A Pre-Treatment for Reverse Osmosis

Abstract: Reverse osmosis is widely used as one of the most effective and advanced technologies for the treatment of leachate from landfill sites. Unfortunately, high leachate contamination—above all, ammonia nitrogen—affects membrane selectivity and is reflected in permeate quality. Furthermore, iron contained in leachate can facilitate chelates forming, which reduces the membrane anti-fouling capacity. The addition of a pre-treatment step could alleviate the adverse impact of the pollutants. As such, we investigated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[ 11 ] LL is one of the most difficult wastewaters to treat because of its varied composition, particularly its high organic and total ammonia nitrogen (TAN) load. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] LL is one of the most difficult wastewaters to treat because of its varied composition, particularly its high organic and total ammonia nitrogen (TAN) load. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[11] LL is one of the most difficult wastewaters to treat because of its varied composition, particularly its high organic and total ammonia nitrogen (TAN) load. [12] In biological treatment processes, microorganisms play an essential role in the biodegradation of organic contaminants, which are simple, economical, attractive, and ecofriendly in nature. [13] Due to its low cost and applicability, biological treatment is widely employed to remove the bulk of the COD in the leachate, thus, minimizing future liquid and gaseous emissions.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22], Chlorella sp. [1,[22][23][24][25][26][27][28][29][30][31][32][33], Desmodesmus sp. [23,34], Picochlorum sp.…”
Section: Introductionmentioning
confidence: 99%
“…[23,28]; and even a consortium of microalgae [20] have been studied. Table 1 shows that the most reported concentration of leachate is 10% v/v [20,22,23,[28][29][30]33]; however, some authors claim that higher concentrations of leachate (from 20%, up to undiluted leachate) can also be used by algae and cyanobacteria [24,26,32,36]. In a different approach, Kumari et al [37] demonstrated that a microalgae-bacteria consortium (Scenedesmus sp.…”
Section: Introductionmentioning
confidence: 99%